MC5R Contributes to Sensitivity to UVB Waves and Barrier Function in Mouse Epidermis - Akari Shintani; Hiromi Sakata-Haga; Keiichi Moriguchi; Mitsuhiro Tomosugi; Daisuke Sakai; Tsuyoshi Tsukada; Makoto Taniguchi; Masahide Asano; Hiroki Shimada; Hiroki Otani; Hiroki Shoji; Junko Hatta; et al. (Elsevier, 2021)
MC5R is known for its role in the exocrine function of sebaceous glands, but other functions in the epidermis remain unclear. This study focused on the relationship between MC5R and homeostasis in the epidermis and examined the role of MC5R in mice whose skin was irradiated with UVB waves. UVB irradiation-induced skin ulcers and severe inflammation at lower doses in homozygotes of MC5R-deficient (i.e., MC5R−/−) mice (150 mJ/cm2) than the doses in wild-type mice (500 mJ/cm2). Transepidermal water loss was increased (approximately 10-fold) in adult MC5R−/− mice compared with that in wild-type mice. In neonates, a dye exclusion assay showed no remarkable difference between MC5R−/− and wild-type mice. After UVB irradiation, compared with wild-type mice, MC5R−/− mice showed increased inflammatory cell infiltration in the dermis of the ulcerative region, significantly increased thickness of the epidermis in the nonulcerative region, significantly more prickle cells in the nonulcerative region, and increased serum IL-6 levels but decreased IL-10 levels. Transmission electron microscopy revealed fewer lamellar granules, less lipid secretion, and an expansion of the trans-Golgi network in the epidermis in MC5R−/− mice. This study elucidated the increased sensitivity to UVB irradiation and decreased barrier function in MC5R−/−mice.